DEVELOPMENT OF E-MODULES TO IMPROVE PERSONAL AND IMAGINATIVE WRITING SKILLS IN ELEMENTARY SCHOOL - Kiki Aniskasari; Syamsul Hadi; Dedi Kuswandi (Universitas Islam Negeri Mataram, 2025)
This research is motivated by the low ability to write personal and imaginative reclaimed texts in grade III students in one of the elementary schools in Malang. Based on the results of observations and interviews with class teachers, it was found that students had difficulty in compiling ideas sequentially, using language according to the rules, and understanding the structure of the recon text. The objectives of this study are (1) to produce an interactive e-module that is feasible, practical, interesting, and effective to be used in learning to write personal and imaginative rekon texts in grade III elementary school students, and (2) to analyze the effectiveness of the interactive e-module in improving the ability to write personal and imaginative rekon texts. This research uses the Dick and Carey research and development method. The results of the study showed that (1) the interactive e-module was declared feasible to use with a media expert validation score of 100% very feasible and a material expert of 73% feasible; (2) the practicality aspect obtained an average score of 90% practical; (3) the attractiveness aspect obtained an average score of 93% attractive; and (4) the effectiveness aspect is shown by the increase in student learning outcomes with an N-Gain value of 0.80 (high category), where all students achieve scores above the KKM and can write the remastered text in a complete, orderly, logical and in accordance with linguistic rules